Ovarian stem cells—resolving controversies - Bhartiya, Deepa (J Assist Reprod Genet, 2017)
A recent review on ovarian stem cells by Horan and Williams entitled “Oocyte Stem Cells: Fact or Fantasy?” suggests that the debate on ovarian stem cells (OSCs) is still not over. They did not even discuss the presence of two distinct populations of stem cells in the ovary in their review. OSCs are located in the ovary surface epithelium and Tilly’s group reported them in the size range of 5–8 μm whereas Virant-Klun’s group has reported pluripotent, 2–4 μm OSCs. Our group reported OSCs of two distinct sizes including pluripotent very small embryonic-like stem cells (VSELs) which are smaller in size than RBCs (similar to those reported by Virant-Klun’s group) and slightly bigger (similar to those reported by Tilly’s group) tissue committed progenitors (OSCs) that presumably differentiate from VSELs. These stem/progenitor cells express receptors for follicle stimulating hormone (FSH) and are activated by FSH. Our opinion article provides explanation to several open-ended questions raised in the review on OSCs by Horan and Williams. VSELs survive chemotherapy; maintain life-long homeostasis; loss of their function due to a compromised niche results in age-related senescence and presence of overlapping pluripotent markers suggest that they may also be implicated in epithelial ovarian cancers.